A Rare Case of Pure Erythroid Sarcoma in a Pediatric Patient: Case Report and Literature Review - Pablo Manresa; Fabián Tarín; María Niveiro; María Tasso; Olga Alda; Francisco López; Héctor Sarmiento; José J. Verdú; Francisco De Paz; Silvia López; María Del Cañizo; Esperanza Such; et al. (MDPI AG, 2017)
We describe an exceptional case of erythroid sarcoma in a pediatric patient as a growing orbital mass with no evidence of morphologic bone marrow involvement, who was finally diagnosed of pure erythroid sarcoma based on histopathology and flow cytometry criteria. We discuss the contribution of standardized eight-color flow cytometry as a rapid and reliable diagnostic method. The use of normal bone marrow databases allowed us to identify small aberrant populations in bone marrow and later confirm the diagnosis in the neoplastic tissue.